Packaging para bebidas naturales y comida tradicional para el mercado 10 de noviembre de la ciudad de Guaranda Provincia de Bolívar - Betancourth Pastrano, Erick David (2020)
The purpose of this research is to contribute to society through a packaging design as a mean to boost the local economy, contributing to the recognition of natural drinks, traditional food and “10 De Noviembre” Guaranda’s market, the project is aimed at the inhabitants of 18 to 50 years. The need has arisen due to the lack of packaging for drinks and food in relation to the protection and mobilization of the aforementioned products. According to the field research, it was determined that the market retains a wide range of products, which make it commercial, which is why a packaging capable of communicating and motivating the purchase of the aforementioned products is required, for this purpose, the Ambrose and Harris methodology, taking seven of its twelve phases, for the development of the proposal, such as: first, definition, where the need of the project is identified; second, research, where surveys and interviews were applied; third, ideation, the ideas for packaging and packaging were developed here; fourth, prototype, tests are carried out to know the best form of packaging. Peredo Álvaro's methodology was applied to the development of the graphics in its four phases, the first is the investigation where the brief carried out on the merchants was analyzed, second coding in which the elements for the market brand were identified, third Production here the representative elements found in the products and the typography are illustrated, fourth printing where the graphics that will be present in the prototype of the packaging are generated. For the development of the project, field research was used that allows a recording of the photographic and visual resources of the prototype, providing results that allowed evaluating the reception of the proposal both in merchants and consumers.